Optimization of delay and temperature for improved design flow in 3D IC - Thomas, Simi P; Chandran, Reshma; Elizabeth Abraham, Neethan; Thomas, Sunu Ann (International Journal of Computer Sciences and Engineering, 2025)
Thermal issue is a critical challenge in 3D IC design. To eliminate hotspots, physical layouts are always adjusted by shifting or duplicating hot blocks. However, these modifications may degrade the packing area as well as interconnect distribution greatly. In this paper, we propose some novel thermal-aware incremental changes to optimize these multiple objectives including thermal issue in 3D ICs. Furthermore, to avoid random incremental modification, which may be inefficient and need long runtime to converge, here potential gain is modeled for each candidate incremental change. Based on the potential gain, a novel thermal optimization flow to intelligently choose the best incremental operation is presented. We distinguish the thermal-aware incremental changes in three different categories: migrating computation, growing unit and moving hotspot. Mixed integer linear programming (MILP) models are devised according to these different incremental changes. Experimental results show that migrating computation, growing unit and moving hotspot can reduce max on-chip temperature by 7%, 13% and 15% respectively on MCNC/GSRC benchmarks. Still, experimental results also show that the thermal optimization flow can reduce max on-chip temperature by 14% compared to an existing 3D floorplan tool CBA, and achieve better area and total wirelength improvement than individual operations do.